2020
DOI: 10.1186/s40246-020-00281-5
|View full text |Cite
|
Sign up to set email alerts
|

A de novo frameshift pathogenic variant in TBR1 identified in autism without intellectual disability

Abstract: Background In order to be able to provide accurate genetic counseling to patients with Autism Spectrum Disorder (ASD), it is crucial to identify correlations between heterogeneous phenotypes and genetic alterations. Among the hundreds of de novo pathogenic variants reported in ASD, single-nucleotide variations and small insertions/deletions were reported in TBR1. This gene encodes a transcription factor that plays a key role in brain development. Pathogenic variants in TBR1 are often associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The gene T-brain 1 (TBR1) encodes the transcription factor TBR1, which mediates gene transcription and cortical neurogenesis and is crucial for normal neurodevelopment. Several preclinical and clinical studies have shown TBR1 to be implicated in ASD [57][58][59][60][61]. TBR1 haploinsufficiency results in defective axonal projections of amygdala neurons and impairs social interaction, memory, cognitive flexibility [58], and neuronal activation of the olfactory system in mice models [57].…”
Section: Brain Changes Associated With Genetic Changes In Asd Structu...mentioning
confidence: 99%
“…The gene T-brain 1 (TBR1) encodes the transcription factor TBR1, which mediates gene transcription and cortical neurogenesis and is crucial for normal neurodevelopment. Several preclinical and clinical studies have shown TBR1 to be implicated in ASD [57][58][59][60][61]. TBR1 haploinsufficiency results in defective axonal projections of amygdala neurons and impairs social interaction, memory, cognitive flexibility [58], and neuronal activation of the olfactory system in mice models [57].…”
Section: Brain Changes Associated With Genetic Changes In Asd Structu...mentioning
confidence: 99%
“…FOXP2 and TBR1 are the L6 markers. TBR1 is a T-box brain transcription factor that was identified in patients with ASD and ID (Nambot et al 2020 ; Sapey-Triomphe et al 2020 ; Vegas et al 2018 ), has been shown to regulate cortical lamina formation, differentiation of L6, dendritic patterning, and inhibitory synaptic density during development (Co et al 2022 ; Fazel Darbandi et al 2018 ; Bedogni et al 2010 ). Tbr1 haploinsufficiency in mice resulted in axonal projection defects in amygdala neurons and impairments in social interaction, USVs, and cognitive flexibility (Huang et al 2014 ).…”
Section: Cortical Deep Layers Underlying Socialitymentioning
confidence: 99%